2014
DOI: 10.1002/nav.21600
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the value of demand sharing in supply chains

Abstract: We consider the problem of assessing the value of demand sharing in a multistage supply chain in which the retailer observes stationary autoregressive moving average demand with Gaussian white noise (shocks). Similar to previous research, we assume each supply chain player constructs its best linear forecast of the leadtime demand and uses it to determine the order quantity via a periodic review myopic order‐up‐to policy. We demonstrate how a typical supply chain player can determine the extent of its availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…This finding is not without contradictory to some studies such as that of Giloni et al. (2014) and Kovtun et al. (2014).…”
Section: Introductioncontrasting
confidence: 52%
See 2 more Smart Citations
“…This finding is not without contradictory to some studies such as that of Giloni et al. (2014) and Kovtun et al. (2014).…”
Section: Introductioncontrasting
confidence: 52%
“…By contrast, previous research concluded that information sharing is only useful in the setting of positively correlated demand. This finding is not without contradictory to some studies such as that of Giloni et al (2014) and Kovtun et al (2014). The authors provide some theoretical results, which suggest that information sharing in case of a pure AR(1) retail demand would hold no value when a manufacturer can recover the retailer's information in terms of demand shocks from its invertible ARMA (1,1) order demand.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation